2014
DOI: 10.1124/mol.114.091587
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Key Residues in Transmembrane 4 Responsible for the Secondary, Low-Affinity Conformation of the Humanβ1-Adrenoceptor

Abstract: The b 1 -adrenoceptor exists in two agonist conformations/states: 1) a high-affinity state where responses to catecholamines and other agonists (e.g., cimaterol) are potently inhibited by b 1 -adrenoceptor antagonists, and 2) a low-affinity secondary conformation where agonist responses, particularly CGP12177 [(2)-4-(3-tert-butylamino-2-hydroxypropoxy)-benzimidazol-2-one] are relatively resistant to inhibition by b 1 -adrenoceptor antagonists. Although both states have been demonstrated in many species (includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 34 publications
(69 reference statements)
1
28
0
Order By: Relevance
“…Site‐directed mutagenesis studies have attempted to isolate the regions of the β 1 ‐adrenoceptor responsible for this second site pharmacology in CHO‐K1 cells (Baker et al. , ; Joseph et al. 2004b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Site‐directed mutagenesis studies have attempted to isolate the regions of the β 1 ‐adrenoceptor responsible for this second site pharmacology in CHO‐K1 cells (Baker et al. , ; Joseph et al. 2004b).…”
Section: Introductionmentioning
confidence: 99%
“…Baker et al. () have indicated that residues within the dimer interface region in transmembrane domain (TM) 4 of the β 1 ‐adrenoceptor may be responsible for the secondary β 1 ‐adrenoceptor conformation (Gherbi et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…This cDNA was also subcloned as a HindIII/XbaI fragment into pcDNA3.1, and the sequence was confirmed by DNA sequencing. The mutations described in Table 1 were generated using QuikChange mutagenesis and BioLine PolyMate Additive for GC-rich templates (Baker et al, 2014). After subcloning in Top 10F competent cells, each mutant b2-adrenoceptor cDNA was excised on HindIII/XbaI and subcloned into native pcDNA3.1 containing a neomycin selection marker.…”
Section: Molecular Biologymentioning
confidence: 99%
“…Following mutagenesis, each receptor DNA was digested with VspI, the fragments were purified, and the alternative N terminal sequences were ligated to give a b1-adrenoceptor with the full b2-adrenoceptor N terminus (b1-N) or a b2-adrenoceptor with the full b1-adrenoceptor N terminus (b2-N). These constructs were expressed in Chinese hamster ovary (CHO)-K1 cells, and stable cell lines were generated (see below and Baker et al, 2014). Once important EL or TM regions for the interaction of salmeterol were identified, to determine which individual amino acids were involved, several single-point mutations and chimeric receptors were made (Table 1), and these constructs were expressed transiently in CHO-K1 cells.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation